Race and Ethnic Differences in College Achievement: Does High School Attended Matter? - Fletcher, Jason M. (2010)
This paper uses 10 years of enrollment data at four Texas public universities to examine whether, to what extent, and in what ways high school attended contributes to racial and ethnic differences in college achievement. Like previous studies, we show that controlling for observable pre-college achievement variables (e.g. test scores, class rank) shrinks, but does not eliminate, sizable racial differences in college achievement. Fixed-effects models that take into account differences across high schools that minority and nonminority youth attend largely eliminate, and often reverse, black-white and Hispanic-white gaps in several measures of college achievement. Our results, which are quite robust across universities of varying selectivity, illustrate how high school quality foments race and ethnic inequality in postsecondary achievement. Leveling inequities in the quality of high schools that minority students attend is a long-run agenda, but remediation programs that compensate for instructional shortfalls at low performing high schools may help close achievement gaps in the interim.